First detection of two cycloviruses in cormorant fecal samples in China by high-throughput sequencing technology - Pei, Yifei; Cai, Shiyu; Xue, Yue; Fu, Yutong; Zhang, Jingyue; Shen, Quan; Ji, Likai; Wu, Ping; Wang, Hua; Wang, Yan; Zhang, Wen; Yang, Shixing (Frontiers in Veterinary Science, 2025)
IntroductionThe Great Cormorant (Phalacrocorax carbo) is widely distributed across China. As an apex predator in aquatic ecosystems, it plays a tripartite ecological role: acting as a natural host, transmission vector, and indicator species for viruses. Current research confirms that cormorants carry diverse viral pathogens from the families including Flaviviridae, Orthomyxoviridae, Paramyxoviridae, and Polyomaviridae. Significant knowledge gaps persist regarding their virome diversity.MethodsIn this study,46 cormorant fecal swab samples were collected at Xiamen Garden Expo Park, and viralmetagenomics method was conducted to identify two Cycloviruses.ResultsThis study identified two novel cycloviruses, Corcyclo-1 (1,856 bp) and Corcyclo-2 (1,831 bp), from cormorant fecal samples using viral metagenomics. Genomic analyses revealed hallmark features of the genus Cyclovirus, including inversely oriented open reading frames (ORFs) encoding the capsid protein (Cap) and replication-associated protein (Rep), as well as a conserved stem-loop sequence TAATACTAT. The Rep gene of Corcyclo-1 contained a 166-bp intron and shared >96.9% amino acid identity with human-, wild boar-, and chicken-derived cyclovirus strains (HaCV-8) from Vietnam and Madagascar, classifying it as a novel strain of HaCV-8. In contrast, Corcyclo-2 harbored a 98-bp intron in its Rep gene and clustered with unclassified cyclovirus strains from bats and mongooses in China and Saint Kitts and Nevis (>97.4% identity), constituting a putative new species. Phylogenetic and pairwise sequence analyses further supported their taxonomic positions. Epidemiological screening demonstrated a high prevalence of Corcyclo-1 (82.6%, 38/46) and Corcyclo-2 (32.6%, 15/46) in cormorant feces. Cross-species surveillance detected Corcyclo-2 in chickens (25.8%, 16/62) and ducks (11.7%, 9/77), whereas Corcyclo-1 was absent in these hosts.ConclusionThis study represents the first report of cormorant-associated cycloviruses, highlighting their potential for cross-species transmission and providing new insights into the ecological diversity and evolutionary mechanisms of cyclovirus.